Examining Developmental Patterns of Prison Misconduct: An Integrated Model Approach - Cihan, Abdullah (International journal of offender therapy and comparative criminology, 2019)
Recent prison scholarship has employed an integrated model of the developmental/life-course perspectives and importation model to examine prison misconduct. Using longitudinal data from a large sample of inmates incarcerated in a U.S. prison system, this study attempts to validate and expand recent prison research by systematically examining the relationship among inmate characteristics and misconduct trajectories, particularly for the higher/chronic pattern of misconduct relative to other identified clusters. The results show that smaller groups of inmates have persistent criminal careers and continually engaged in high level of misconduct. In addition, several inmate characteristics associated with prison misconduct can also be useful to distinguishing high-risk inmates/persistent offenders from groups that offend at low rates over time. These findings could provide vital information to prison officials in developing and designing alternative prison services, assistance, and rehabilitation programs based on the misconduct trajectories.